OP0134 Cut-Offs Values for Inflammatory H-MRI Lesions to Define Remission. Comparison Between DAS28, SDAI and New Boolean ACR/EULAR Criteria. (23rd January 2014) - Lisbona, M.; Maymo, J.; Ares, J.; Almirall, M.; Navallas, M.; Solano, A.; Carbonell, J.
Abstract : Background: The current primary goal of treating patients with rheumatoid arthritis (RA) is achieving clinical remission. Nevertheless many patients in clinical remission have subclinical inflammatory activity by MRI, and some of these patients have shown relevant progression of joint damage over time. It is unknown whether there is a cut-off level for each inflammatory lesion on MRI (bone edema, synovitis and tenosynovitis or a combination of all) associated to RA clinical remission (evaluated by disease activity scores). Objectives: To determine the cut-off values of inflammatory lesions on hand MRI associated to remission and comparing these cut-offs between several composite measures of disease activity in RA patients. Methods: Cross-sectional study. For the selection of cut-offs we used data from CRC-hand MRI register of Hospital del Mar (PSMAR, Barcelona, Spain) of RA patients (fulfilling ACR 1987 revised criteria) with various levels of disease activity. Patients from CRC-hand MRI register are an appropriate representation of patients with RA in general (early and established disease, DMARD and biological treatments). Inflammatory MRI scores (bone edema and synovitis) according to the RA MRI Scoring System (RAMRIS), tenosynovitis, sum of all lesions and disease activity composite values were recorded. Receiver operating characteristic (ROC) analysis was used to identify the best cut-off point(s) of hand MRI (h-MRI). The validation of the cut-offs was based on the disease activity category by DAS28, SDAI or new Boolean ACR/EULAR criteria. The value with optimum balance between sensitivity and specificity were selected for each inflammatory lesion (RAMRIS synovitis (0-21), RAMRIS bone edema (0-69), tenosynovitis (0-26) and sum of all (Total inflammation (0-116)) and was calculated on statistical grounds. Data evaluation and statistical analysis were performed using SPSS v.15. Results: A total of 388 h-MRI of 196 RA patients were included. One hundred nineteen (30.6%) of the h-MRI corresponded to a DAS28 ≤ 2.6, 22.1% and 21.1% to a SDAI ≤ 3.3 and Boolean ACR/EULAR remission criteria, respectively. The ROC curves analysis identified a values of 6 for synovitis and 8 for total inflammation as the best cut-offs points to differentiate between RA patients in remission or not by all three disease activity scores. Cut-off for bone edema and tenosynovitis were 2 and 5 for DAS28 ≤ 2.6 respectively; however, these cut-offs were low for SDAI and for new boolean ACR/EULAR criteria (bone edema was 1 and tenosynovitis was 3). Considering these cut-offs points, around 60-70% of h-MRI were correctly classified. In general, the validity of the inflammatory MRI cut-offs were moderate in all cases (Table). Conclusions: The discriminative ability of inflammatory h-MRI cut-offs for separate active patients from remission patients were moderate and comparable between different disease activity scores. However, using more stringent remission criteria as SDAI and boolean ACR/EULAR criteria resulted in low cut-off for bone edema and tenosynovitis. Further longitudinal studies are required to evaluate the validity of these inflammatory h-MRI cut-offs to predict later good radiographic and functional outcomes. References: Disclosure of Interest: None Declared